Corruption and Decentralized Public Governance - Shah, Anwar (World Bank, Washington, DC, 2012)
This paper examines the conceptual and empirical basis of corruption and governance and concludes that decentralized local governance is conducive to reduced corruption in the long run. This is because localization helps to break the monopoly of power at the national level by bringing decisionmaking closer to people. Localization strengthens government accountability to citizens by involving citizens in monitoring government performance and demanding corrective actions. Localization as a means to making government responsive and accountable to people can help reduce corruption and improve service delivery. Efforts to improve service delivery usually force the authorities to address corruption and its causes. However, one must pay attention to the institutional environment and the risk of local capture by elites. In the institutional environments typical of some developing countries, when in a geographical area, feudal or industrial interests dominate and institutions of participation and accountability are weak or ineffective and political interference in local affairs is rampant, localization may increase opportunities for corruption. This suggests a pecking order of anticorruption policies and programs where the rule of law and citizen empowerment should be the first priority in any reform efforts. Localization in the absence of rule of law may not prove to be a potent remedy for combating corruption.